2022
DOI: 10.1021/acs.jafc.2c05712
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermostability and Molecular Insights for l-Asparaginase from Bacillus licheniformis via Structure- and Computation-Based Rational Design

Abstract: L-Asparaginase has gained much attention for effectively treating acute lymphoblastic leukemia (ALL) and mitigating carcinogenic acrylamide in fried foods. Due to high-dose dependence for clinical treatment and low mitigation efficiency for thermal food processes caused by poor thermal stability, a method to achieve thermostable L-asparaginase has become a critical bottleneck. In this study, a rational design including free energy combined with structural and conservative analyses was applied to engineer the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 72 publications
2
27
0
Order By: Relevance
“…In addition, the surface net charge of the enzyme has a significant influence on its thermal unfolding and refolding behavior . Increasing the surface net charge by altering the distribution of the surface charge of proteins can enhance the thermal stability of proteins. ,, In the present study, Mut1 and Mut2 constructed by combinational mutations showed significant changes in the surface electrostatic potential in the loop2, loop3, and loop4 regions (Figure ), resulting in an increase in the net surface charge of the mutants in comparison with that of wild-type XynA (Table ). A higher surface net charge can promote reversible refolding by preventing xylanase aggregation.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, the surface net charge of the enzyme has a significant influence on its thermal unfolding and refolding behavior . Increasing the surface net charge by altering the distribution of the surface charge of proteins can enhance the thermal stability of proteins. ,, In the present study, Mut1 and Mut2 constructed by combinational mutations showed significant changes in the surface electrostatic potential in the loop2, loop3, and loop4 regions (Figure ), resulting in an increase in the net surface charge of the mutants in comparison with that of wild-type XynA (Table ). A higher surface net charge can promote reversible refolding by preventing xylanase aggregation.…”
Section: Discussionmentioning
confidence: 53%
“…For example, a BlAsnase variant obtained by site-directed saturation mutagenesis improved its thermal stability by 65.8-fold at 55 °C. 22 Similarly, a thermostable cellobiose CtCel6 from Thermus thermophilus was rationally engineered using site-directed mutagenesis based on structure to give a variant with a halflife (t 1/2 ) increased by 1.42-fold and 2.40-fold at 80 and 90 °C, respectively. 23 Rational and semirational design strategies have been used to identify mutations at five beneficial sites of βglycosidase BglY of T. thermophilus, which were then recombined in variant HF5 to increase the t 1/2 by 4.7-fold at 93 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Approaches such as directed evolution, rational design, and computer-aided design have proven to be effective strategies for engineering thermophilic enzymes. For example, a BlAsnase variant obtained by site-directed saturation mutagenesis improved its thermal stability by 65.8-fold at 55 °C . Similarly, a thermostable cellobiose CtCel6 from Thermus thermophilus was rationally engineered using site-directed mutagenesis based on structure to give a variant with a half-life ( t 1/2 ) increased by 1.42-fold and 2.40-fold at 80 and 90 °C, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme thermostability is crucial for their kinetic stability and robustness . Various strategies have been employed to enhance enzyme thermostability, including the introduction of disulfide bonds, proline modification, salt bridge formation, and charge on the protein surface .…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme thermostability is crucial for their kinetic stability and robustness. 13 Various strategies have been employed to enhance enzyme thermostability, including the introduction of disulfide bonds, 14 proline modification, 15 salt bridge formation, 16 and charge on the protein surface. 17 Among these strategies, the incorporation of disulfide bonds has gained significant attention due to their ability to reduce the entropy of the unfolded state, 18 thus improving protein thermostability.…”
Section: Introductionmentioning
confidence: 99%